Cytologic diagnosis of acinic cell carcinoma of minor salivary gland: a distinct rarely described entity - Rana Sherwani; Kafil Akhtar; Murad Ahmad; Abrar Hasan (Clinics and Practice, 2011)
A rare case of acinic cell carcinoma of minor salivary gland with cervical lymph node metastasis in a 50-year-old man is reported and the literature regarding this type of tumor is reviewed. These tumors arise from either an intercalated duct stem cell or the reserve cell of the salivary gland terminal tubule but not from both simultaneously. Rarely these neoplasms arise from more mature acinar cells. It is clear that these tumors behave ominously. The 25 year determinate survival rate is 50%, with a 20% incidence of metastasis. Surgical excision is the treatment of choice. Radiotherapy, especially neutron therapy, has a place in the treatment of this tumor but the role of chemotherapy is not exactly known at this time.